Всемирная история - Пономарев М. В. (Современная школьная энциклопедия, 2008)
Экземпляры: СФ-16 (20101120) / Инвентарный номер: 38270z16 / Цена: 235.20 / Сис.шифр: 63.3(0) / Авт.знак: В 84 / ГРНТИ: 03.09 / ББК: 63.3(0)